2022
DOI: 10.1186/s40164-022-00277-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the tumor immune microenvironment and its clinical relevance

Abstract: During the course of tumorigenesis and subsequent metastasis, malignant cells gradually diversify and become more heterogeneous. Consequently, the tumor mass might be infiltrated by diverse immune-related components, including the cytokine/chemokine environment, cytotoxic activity, or immunosuppressive elements. This immunological heterogeneity is universally presented spatially or varies temporally along with tumor evolution or therapeutic intervention across almost all solid tumors. The heterogeneity of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 172 publications
(170 reference statements)
2
43
0
Order By: Relevance
“…Most patients show a limited sensitivity to these approaches due to tumor heterogeneity while several treatments have already brought therapeutic efficacy for LGG patients [ 6 ]. Given the crucial role of the tumor immune microenvironment in tumor heterogeneity, immunotherapy has been considered as a novel promising therapy against various solid tumors [ 7 ]. Recently, more and more studies have focused on the impact of immune checkpoint inhibitors (ICIs) on the prognosis of LGGs.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients show a limited sensitivity to these approaches due to tumor heterogeneity while several treatments have already brought therapeutic efficacy for LGG patients [ 6 ]. Given the crucial role of the tumor immune microenvironment in tumor heterogeneity, immunotherapy has been considered as a novel promising therapy against various solid tumors [ 7 ]. Recently, more and more studies have focused on the impact of immune checkpoint inhibitors (ICIs) on the prognosis of LGGs.…”
Section: Introductionmentioning
confidence: 99%
“…Another important source of HER2-positive BC heterogeneity might be related to its underlying tumor immune microenvironment (TIM) [16]. Immune cells and immune checkpoints in TIM are the executors of immune clearance, surveillance and tolerance of the body against tumors [17]. This finding gave a comprehensive understanding of COL12A1 on the infiltration of CD8+ T cells, NK cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-tumoural heterogeneity (also known as inter-lesion heterogeneity) refers to the variations of different tumour genotypes among patients, even within the same histological subtypes [ 32 , 33 ]. Upon evaluating the single-cell transcriptional program from 19 metastatic melanoma tumours, Tirosh et al identified a rare therapy-resistant subpopulation of melanoma cells expressing high levels of AXL Receptor Tyrosine Kinase inside the heterogenous tumours harbouring MITF (microphthalmia-associated transcription factor) due to clonal selection after targeted treatment with RAF/MEK inhibition [ 34 ].…”
Section: Insights Into Heterogeneity Of Tumour Microenvironment From ...mentioning
confidence: 99%
“…Heterogeneity in the tumour is not only limited to cancer cells, but also influences peritumoural stroma cells, tumour-infiltrating lymphocytes, and other stimulatory/inhibitory elements [ 33 , 40 ]. This heterogeneity includes spatial heterogeneity, which describes the non-uniform distribution of genetically diverse clonal populations across different disease sites or within a single site or tumour, and temporal heterogeneity, a term applied to polyclonal features of an individual tumour that evolve over time (i.e., heterogeneity between the primary tumour and a subsequent local or distant recurrence within a patient) [ 28 , 41 , 42 ].…”
Section: Insights Into Heterogeneity Of Tumour Microenvironment From ...mentioning
confidence: 99%